TINJAUAN YURIDIS IMPLEMENTASI UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA DALAM PERJANJIAN KERJA (STUDI PENELITIAN PT AGRICON PUTRA CITRA OPTIMA): - Farida Mukhlisah; Wiratno (Faculty of Law, Universitas Trisakti, 2023)
Law Number 11 of 2020 concerning Job Creation changes several provisions regarding employment which were previously regulated in Law Number 13 of 2003 concerning Employment (“UU Ketenagakerjaan”). The problems in this research include: 1) What are the work agreement procedures made between PT Agricon Putra Citra Optima and workers who work at the company? 2) Is the agreement at PT Agricon Putra Citra Optima in accordance with Law Number 11 of 2020 concerning Job Creation? The research method used is normative juridical research with legal material collection techniques using literature studies and interviews. The research results show that the procedure for making a certain time work agreement made by PT Agricon Putra Citra Optima with workers who work for the company has been made in accordance with the provisions. However, the specific time work agreement made by PT Agricon Putra Citra Optima with its workforce contained errors regarding the type of work agreed to in the work agreement. This is because the work that must be done by workers is not included in the work criteria for which a fixed-term work agreement can be made according to the provisions contained in Law Number 11 of 2020.